Postprandial plasma betaine and other methyl donor-related responses after consumption of minimally processed wheat bran or wheat aleurone, or wheat aleurone incorporated into bread - MOLLOY, ANNE (My University, 2015)
The bran and particularly the aleurone fraction of wheat are high in betaine and other physiological methyl donors, which may exert beneficial physiological effects. We conducted two randomised, controlled, cross-over postprandial studies to assess and compare plasma betaine and other methyl donor-related responses following the consumption of minimally processed bran and aleurone fractions (study A) and aleurone bread (study B). For both studies, standard pharmacokinetic parameters were derived for betaine, choline, folate, dimethylglycine (DMG), total homocysteine and methionine from plasma samples taken at 0, 0·5, 1, 2 and 3 h. In study A ( n 14), plasma betaine concentrations were significantly and substantially elevated from 0·5 to 3 h following the consumption of both bran and aleurone compared with the control; however, aleurone gave significantly higher responses than bran. Small, but significant, increases were also observed in DMG measures; however, no significant responses were observed in other analytes. In study B ( n 13), plasma betaine concentrations were significantly and substantially higher following consumption of the aleurone bread compared with the control bread; small, but significant, increases were also observed in DMG and folate measures in response to consumption of the aleurone bread; however, no significant responses were observed in other analytes. Peak plasma betaine concentrations, which were 1·7 – 1·8 times the baseline levels, were attained earlier following the consumption of minimally processed aleurone compared with the aleurone bread (time taken to reach peak concentration 1·2 v. 2·1 h). These results showed that the consumption of minimally processed wheat bran, and particularly the aleurone fraction, yielded substantial postprandial increases in plasma betaine concentrations. Furthermore, these effects appear to be maintained when aleurone was incorporated into bread
Keywords: aleurone fraction of wheat; aleurone fraction of wheat